Role of learners’ ethnosociocultural competence in written language learning: case of argumentative text - Khireddine, Nadia; Slitane, Kamel (El Omda in Linguistics and Discourse Analysis, 2023)
In this study, we focus on learners’ ethnosociocultural competence as an important factor in the process of written language learning. To this end, we first attempt to identify the representations that constitute this competence, and then examine the impact they may have on learners’ success or failure in written tasks (comprehension and production). The study was conducted with 4th-year middle school students.